Multilocation evaluation of protein hydrolysates (20 %) foliar application on growth and yield of chickpea under diverse agro-climatic conditions in India - Jagadeesh , U; Sparjan , B D S; Ajay, P P; Ankita, N; Nagendra, P; Sindhu, B; Ganesh, D; Rajesh, K S (Plant Science Today, 2026)
Protein hydrolysates, composed of amino acids and short-chain peptides, have gained prominence as effective bio-stimulants that enhance nutrient uptake, enzymatic activity and overall crop productivity. Chickpea (Cicer arietinum L.), a vital pulse crop, often suffers yield losses due to soil fertility constraints and climatic variability. However, multilocation dose-response information on protein hydrolysates in chickpea under contrasting environments remains limited. To address this, a multilocation field study was undertaken during the rabi season of 2024-25 to evaluate the bio-efficacy of a 20 % protein hydrolysate formulation applied as a foliar spray at different concentrations across three agro-climatic regions at Dr PDKV, Akola; DBSKKV, Karjat and KSNUAHS, Shivamogga. The experiment followed a randomised block design (RBD) with five treatments-control, 2.0 mL/L, 3.0 mL/L, 4.0 mL/L and a commercial check and observations were recorded on growth and yield attributes. Improvements in chlorophyll index and nodulation (where measured) suggested enhanced physiological activity contributing to yield improvement. Results revealed that foliar application of protein hydrolysate significantly enhanced plant height, branching, pod number and grain yield across all locations. The 3.0 mL/L concentration showed the most consistent agronomic response, with yield increases of 16.4 % at Akola, 22.5 % at Karjat and 54.69 % at Shivamogga compared to the control. Economic analysis indicated positive returns, supporting practical field applicability. The study indicates that foliar application of 20 % protein hydrolysate at 3.0 mL/L can improve chickpea productivity under diverse agro-climatic conditions and may serve as a sustainable crop management input.